Clinical Experience with Timolol and Brinzolamide Fixed-combination: A Case Series - S. V. Yanchenko; Sh. J. Teshaev; S. S. Davlatov; N. Yu. Khuddieva (Oftalʹmologiâ)
One of the approaches to improve the adherence of patients with primary open-angle glaucoma (POAG) to IOP-lowering eye drops therapy is the use of fixed-combinations (FC), since this makes it possible to reduce treatment cost during combined therapy, reduce the number of instillations per day, minimize the risk of “missing” instillations and reduce the effect of the eye drops preservative on the ocular surface. Increasing patient compliance may also be associated with the use of generics that have pharmacological and therapeutic equivalence to original drugs at a lower cost. The article presents the clinical cases generic 1.0 % brinzolamide + 0.5 % timolol FC instillations in POAG patients. The 1st-clinical case demonstrates comparable efficacy and safety of the generic brinzolamide + timolol FC, compared with the original medication, which is confirmed by the data of a number of authors (A.V. Sidorova et al., 2023), and allows us to talk about the possibility of patients transition from the original to the reproduced eye drops to minimize the cost of therapy. The 2nd-clinical case illustrates the possibility and effectiveness of starting with combined IOP-lowering therapy (based on generic brinzolamide + timolol FC instillation) at the II-stage of POAG with high IOP level, as well as at the III-stage of POAG with an extremely high initial IOP level (brinzolamide + timolol FC and 0.03 % bimatoprost instillations). The 3rd-clinical case shows that generic timolol + brinzolamide FC can be effectively used during maximum-IOP-lowering therapy in combination with prostaglandin and brimonidine.